The Late Ottoman Ulema’s Constitutionalism - Gunasti, Susan (Islamic law and society, 2016)
By examining laws and proposals related to constitutional amendments, the Mecelle, and sharī‘a courts in the 1908–1912 Ottoman parliament, I attempt to explain how ulema in parliament tried to implement their understandings of constitutionalism and legal reform within the legislative framework of the period as set against the framework of parliamentary politics. I focus on the upper-level ulema members of the Chamber of Deputies as they worked to implement their understandings of law and constitutionalism and followed a political strategy to achieve their goals. Based on my study of the draft constitution, official parliamentary publications, and the popular press, I identify the understandings of legal reform that underpinned their proposals and how they influenced the constitutional amendment process, by contrast to the failure of their efforts to expand the Mecelle and reform the sharī‘a courts.